Georges Grosz y los malos humos de Moloc - Lesmes González, Daniel (Anales de Historia del Arte, 2006)
Elias Canetti described George Grosz as one more of the characters that Grosz appeared to criticize. This article takes a deeper look at the works and texts through which, between 1919 and 1921, Grosz stripped Expresionism of its mysticism, inverted the Dadaist nihilism, and, made the motifs of Metaphysics a means of political denouncement. Nevertheless, under the aggressive politicalization of his art, Grosz questioned the movements of the masses whatever its tendency was. Here we scrutinize the contradictions of this verism that more than answering to the Call to Order took pleasure in slicing into disorder.